Como garantir a sustentabilidade do ecoturismo e a conservação do boto-cinza, uma espécie ameaçada de extinção? - Freitas, Diana Carvalho de (2018)
The Coastal Wildlife Reserve of Tibau do Sul (REFAUTS), Pipa beach, Rio Grande do Norte, receives national and international tourists throughout the year. At the REFAUTS is carried out the Guiana dolphin watching (Sotalia guianensis), a species that is threatened of extinction in the national territory. Guiana dolphins that occur at the REFAUTS can be seen daily in the Dolphins and Madeiro bays. The objective of this study was to (i) evaluate the activity of Guiana dolphin watching, investigating the conduct of the boats during the tour in relation to the developed speed, duration of the tour, length of stay in the bays and distance to the coast; and (ii) investigate the flow of tourists at the REFAUTS, analyzing in which subareas there is a greater flow of tourists, which activities are developed and the time of the most intense use of the REFAUTS. Data collection occurred in 2016 and 2017, totaling 20 days of sampling, in the Dolphins and Madeiro bays, restricted and controlled use zone of REFAUTS and in the Central beach, buffer zone of REFAUTS. To achieve the first objective, GPS navigation devices were used to record speed, length of the tour, length of stay in the bays and distance of the boats to the coast. In order to reach the second objective, the census of the tourists in the two bays was carried out every 20 min, and through the use of imaginary lines, the bays were subdivided into subareas so that to understand which subareas were preferred by the tourists. The Guiana dolphin watching presented low compliance with the legislation in force at the REFAUTS (Municipal Law nº 349/2007), in relation to the speed, which should not exceed 4 knots, length of stay, which should not exceed 20 min, and distance to the coast, which should not be less than 200 m. The REFAUTS received tourists who mainly performed the following leisure and/or sport activities: use of stand up paddle, kayaking, surfing, swimming and going on tours on the boats to observe the Guiana dolphin. These tourists, carrying out various activities, have divided the same space among themselves and with the Guiana dolphins. This overlap in the use of areas and the lack of compliance of the boats with Municipal Law nº 349/2007 may be causing too much pressure on the Guiana dolphins. The effective supervision of the boats conduct and the implementation of an environmental zoning at the REFAUTS are measures that must be taken to guarantee the sustainability of the tourism in this Reserve and the long-term conservation of the Guiana dolphin